Evaluation of microbiological and physico‐chemical parameters of retail ready‐to‐eat mono‐varietal salads. Issue 7 (5th April 2019) - Gaglio, Raimondo; Miceli, Alessandro; Sardina, Maria T.; Francesca, Nicola; Moschetti, Giancarlo; Settanni, Luca
Abstract: An integrated microbiological and physico‐chemical approach was applied to evaluate the decay of mono‐varietal ready‐to‐eat escarole ( Cichorium endivia var. latifolium ) and red chicory ( Cichorium intybus L. var. foliosum Hegi) during refrigeration. Total mesophilic microorganisms, including pseudomonads, and total psychrotrophic microorganisms were detected at high numbers in all samples just after packaging and at the expiry date. The dominant microbial populations analyzed by classical culture‐dependent methods belonged to Pseudomonas and yeasts. Illumina sequencing identified Janthinobacterium lividum and Pseudomonas veronii as main species. Regarding the physico‐chemical quality between the beginning and at the end of the expiry date, the main differences were found for weight loss, higher for escarole, and titratable acidity and lightness, higher for red chicory. This work showed how the microbiological and physico‐chemical shelf life parameters changed during storage for escarole and red chicory, even though the cold chain was strictly applied and kept under control. Practical applications: The evaluation of the microbiological, chemical, and physical qualities of mono‐varietal escarole and red chicy during refrigeration indicated how the viable levels of bacteria and yeasts, microbial composition, weight loss, titratable acidity, ascbic acid content, lightness, yellowness, and redness as well as visual quality changed over time. These findings are useful to understand the change of quality parameters of some of the most common vegetable ingredients of mixed salads.